2013
DOI: 10.1111/bcp.12165
|View full text |Cite
|
Sign up to set email alerts
|

Severity of the TGN1412 trial disaster cytokine storm correlated with IL‐2 release

Abstract: Aim To determine if cytokine release with a solid phase assay is predictive of adverse responses for a range of therapeutic mAbs.Methods Cytokine ELISAs and a multi-array system were used to compare responses generated by different therapeutic mAbs using a solid phase assay. Flow cytometry was employed to determine the cellular source of those cytokines.Results Only TGN1412 and muromonab-CD3 stimulated CD4+ T-cell mediated cytokine release characterized by significant (all P < 0.0001) IFNγ, TNFα, IL-2, IL-4, I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 38 publications
3
45
0
Order By: Relevance
“…In our study, we confirmed the absence of induced proliferation with CD28.2, but recorded significant levels of IFNγ, TNF, IL-6 and IL-12 release. Otherwise, whereas the severity of the adverse response of TGN1412 was correlated with the level of IL-2 release, 30 we observed that level of IFNγ release could be more predictive of agonist properties of divalent anti-CD28 mAbs.…”
Section: Mabs Volume 6 Issuementioning
confidence: 57%
“…In our study, we confirmed the absence of induced proliferation with CD28.2, but recorded significant levels of IFNγ, TNF, IL-6 and IL-12 release. Otherwise, whereas the severity of the adverse response of TGN1412 was correlated with the level of IL-2 release, 30 we observed that level of IFNγ release could be more predictive of agonist properties of divalent anti-CD28 mAbs.…”
Section: Mabs Volume 6 Issuementioning
confidence: 57%
“…7A, 7B). In a recent study the severity of the TGN1412-induced cytokine storm was correlated with the IL-2 release, suggesting that IL-2 production might be used as a prognostic factor in upcoming trials of new biologicals (34). Thus, in addition to cytokine secretion, analysis of costimulatory molecules expression may be also informative for the evaluation of new biologicals.…”
Section: Discussionmentioning
confidence: 99%
“…1). Because Eastwood et al (34) showed that IL-2 is a marker associated with the induction of a cytokine storm, we addressed whether under the above conditions T cells were present that secreted TNF-a, IFN-g, and IL-2 in parallel. Irrespective of whether T cells derived from PBMCs or HDC-PBMCs, polyfunctional T cells were detected (Fig.…”
Section: Upon Tgn1412 Treatment T Cells Isolated From High-density Prmentioning
confidence: 99%
“…However, IL2 was combined with an F(ab 0 ) 2 fragment of an anti-CD3/ EpCAM quadroma in a clinical trial (40), but treatment was limited because of considerable toxicity most likely caused by induction of secondary cytokines, known as CRS or cytokine storm. Systemic administration of IL2 is known to induce a cytokine storm (41), and the severity of adverse events associated with CRS, such as with the TGN1412 catastrophic trial, is correlated with IL2 release (42). Although it is not without side effects, immunotherapy with IFNa, which is not produced by T cells, is not typically associated with cytokine storm.…”
Section: Discussionmentioning
confidence: 99%